The importance of multimodal diagnostic methods for therapeutic decision making for overactive bladder in women - Ivanov, Mihaela; Ceban, Emil (Medicine and Pharmacy Reports, 2024)
Background and aim. Despite overactive bladder (OAB) being a symptomatic diagnosis, all patients require a basic assessment to confirm the diagnosis, as well as to exclude any other underlying cause for lower urinary tract dysfunction. While guidelines clearly define different methods of investigations for OAB, there are reasons to believe that these guidelines reflect more of a “one size fits all” model that may not be appropriate for use in all patients. The study aimed to elucidate the complex and advanced multidisciplinary methods of investigation of OAB patients. Methods. PubMed, ScienceDirect, Cochrane Library, and Google Scholar databases were used to search for scientific publications from 2013 to 2023 using relevant keywords and phrases. Results. Data from 708 publications were researched and synthesized, a systematic review was carried out and the detailed and coherent results presented the diagnostic aspects of overactive bladder in women. Relevant citations from selected articles were included, and a synthesis of key information was provided. Conclusion. These discoveries may assist in detecting OAB earlier, allowing for prompt intervention and potentially preventing the condition from progressing to more severe stages and providing healthcare professionals with valuable tools to enhance the diagnosis and treatment of OAB, potentially improving the quality of life for patients affected by this condition.